Prevalence, incidence and chronicity of child abuse among orphaned, separated, and street-connected children and adolescents in western Kenya: What is the impact of care environment?. (May 2023) - Ayaya, Samuel; DeLong, Allison; Embleton, Lonnie; Ayuku, David; Sang, Edwin; Hogan, Joseph; Kamanda, Allan; Atwoli, Lukoye; Makori, Dominic; Ott, Mary A.; Ombok, Caroline; Braitstein, Paula
Abstract: Background: The effect of different types of care environment on orphaned and separated children and adolescents' (OSCA) experiences of abuse in sub-Saharan Africa is uncertain. Objective: Our two primary objectives were 1) to compare recent child abuse (physical, emotional, and sexual) between OSCA living in institutional environments and those in family-based care; and 2) to understand how recent child abuse among street-connected children and youth compared to these other vulnerable youth populations. Participants and setting: This project followed a cohort of OSCA in Uasin Gishu County, Kenya (2009–2019). This analysis includes 2393 participants aged 18 years and below, 1017 from institutional environments, 1227 from family-based care, and 95 street-connected participants. Methods: The primary outcome of interest was recent abuse. Multiple logistic regression was used to estimate the odds of recent abuse at baseline, follow-up, and chronically for each abuse domain and adjusted odds ratios (AOR) between care environments, controlling for multiple factors. Results: In total, 47 % of OSCA reported ever experiencing any kind of recent abuse at baseline and 54 % in follow-up. Compared to those in family-based care, street-connected participants had a much higher reported prevalence of all types of recent abuse at baseline (AOR: 5.01, 95 % CI: 2.89, 9.35), in follow-up (AOR: 5.22, 95 % CI: 2.41, 13.98), and over time (AOR: 3.44, 95 % CI: 1.93, 6.45). OSCA in institutional care were no more likely than those in family-based care of reporting any recent abuse at baseline (AOR: 0.85 95 % CI: 0.59–1.17) or incident abuse at follow-up (AOR: 0.91, 95 % CI: 0.61–1.47). Conclusion: OSCA, irrespective of care environment, reported high levels of recent physical, emotional, and sexual abuse. Street-connected participants had the highest prevalence of all kinds of abuse. OSCA living in institutional care did not experience more child abuse than those living in family-based care.